Financial Difficulties of the Associated Voluntary Hospitals (letter) - Lamb, Sydney
1939-07 1939 1930s 8 pages TELEPHONE: BANK 5050. TELEGRAMS "PENNIPOUND LIVERPOOL." MERSEYSIDE HOSPITALS COUNCIL (INC) 87 LORD STREET LIVERPOOL 2 A1/NEF 14th July, 1939. Sir Walter Citrine, Trades Union Congress, Transport House, Smith Square, LONDON. S.W.1. Dear Sir Walter, FINANCIAL DIFFICULTIES OF THE ASSOCIATED VOLUNTARY HOSPITALS. The Council recently received a letter from the Associated Voluntary Hospitals Board calling the attention of this Council to the increasingly serious financial position of the local voluntary hospitals; a copy of that letter is enclosed. Leaders of the Merseyside Hospitals Council, in company with the Chairman of our local Hospitals, recently met our representatives of Organised Labour when a full and frank discussion on this subject took place. The Chairman of the Council has accepted an invitation to meet the Liverpool Trades and Labour Council on 20th July, and in order that you may be conversant with the views of this Council, I enclose a copy of a document which was prepared some 18 months ago, when consideration was being given to ways and means of increasing Hospital revenue. The voluntary hospitals of Merseyside owe much to the splendid support which has been given to them by Organised Labour, and they are confident that the community, with a definite lead from Organised Labour, will see that the existing difficulties are faced with determination. The latest information available has been embodied in the document which I attach herewith. Yours faithfully, Sydney Lamb Sydney Lamb, Secretary. 292/842/2/208-209